2020
DOI: 10.1098/rsbl.2020.0458
|View full text |Cite
|
Sign up to set email alerts
|

Tape lures swell bycatch on a Mediterranean island harbouring illegal bird trapping

Abstract: Mediterranean islands provide shelter and sustenance for millions of migrating birds each year. Humans have historically exploited bird migration through hunting. In Cyprus, trapping birds during their migratory peak is considered a tradition, but has long been against the law. Illegal bird trapping is lucrative, however, with trappers using tape lures that broadcast birdsong to increase capture rates. It results in the slaughter of millions of birds each year. Yet, scientific studies quantifying capture rates… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Based on the phenotypic similarity in plumage and song between Cyprus and Sardinian Warbler, direct interference competition might occur between the species, which studies in other phenotypically similar and closely related species of birds have shown can result in character displacement or competitive exclusion (e.g., Kirschel et al 2009. Indeed, Cyprus Warbler has been shown to be attracted by playback of Sardinian Warbler song in Cyprus (Sebastianelli et al 2020). Further work is thus needed to explore the possible effects of direct interactions between these Sylvia warbler species and how they might influence their coexistence and population dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the phenotypic similarity in plumage and song between Cyprus and Sardinian Warbler, direct interference competition might occur between the species, which studies in other phenotypically similar and closely related species of birds have shown can result in character displacement or competitive exclusion (e.g., Kirschel et al 2009. Indeed, Cyprus Warbler has been shown to be attracted by playback of Sardinian Warbler song in Cyprus (Sebastianelli et al 2020). Further work is thus needed to explore the possible effects of direct interactions between these Sylvia warbler species and how they might influence their coexistence and population dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…In order to maximise capture success, we lured birds to the nets using playback recordings of conspecific songs of detected species at each site. Studies have found that in addition to increasing the capture success of target species, the use of playbacks while using mist nests could also favor capture [ 39 , 40 ], or response [ 41 ] of other species, not targeted by the playback. We checked the nets and removed the birds as quickly as possible, with a maximum delay of 30 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…We used two types of mist-net: 12 9 2.5 m and 12 9 1 m, according to vegetation height. Conspecific playbacks were used to attract the birds, using recordings of the six studied species from www.xeno-canto.org and a recording of Sardinian Warbler obtained in Cyprus (Sebastianelli et al 2020). Each captured individual was aged, sexed and marked with a numbered aluminium band.…”
Section: Study Species and Sample Collectionmentioning
confidence: 99%